Half and half nails: an important sign in the diagnosis of systemic diseases - Liberski, Sławomir; Marczak, Daria (Journal of Education, Health and Sport, 2018)
Half-and-half nails, also called Lindsay's nails, are a highly specific nail abnormalities for chronic kidney disease; however, the occurrence of half-and-half nails in the course of zinc deficiency, liver cirrhosis, pellagra, Kawasaki disease, Crohn's Disease, Behcet's Disease, citrullinemia, hyperthyroidism, systemic cancer therapy, and yellow nail syndrome, as well as in healthy people was also reported. Half-and-half nails can occur on both, fingernails and much less often on toenails, and are usually described as the proximal white part and the brown, pink or red distal band which are sharply demarcated by the transverse line. The pathogenesis of half-and-half nails is still unclear. Factors that may be involved in the pathogenesis of half-and-half nails include an increase in the thickness and number of capillaries in the nail bed, zinc deficiency, hypoalbuminemia, azotemia, and the accumulation of toxic metabolism products in the body.